Penyelesaian Sengketa dalam Pengadaan Tanah bagi Pembangunan Jalan Tol untuk Kepentingan Umum - Mina, Revi Fauzi Putra; Mubarak, Ridho; Muazzul, Muazzul (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
Land issues in North Sumatra, especially in Medan City, still occur frequently, one of which is land acquisition for the construction of toll road infrastructure to accelerate development, facilitate access to production, distribution, and tourism areas, and create new jobs. Although this development accelerates the economic growth of the country and society, disputes related to land acquisition for public interest are inevitable. One of the cases that is the focus of this research is located in Sumatra Province, specifically the jurisdiction of the Medan District Court. The problem of this research is how legal protection for land rights owners due to land acquisition for toll roads and how the consignment process of compensation for land affected by toll road project acquisition. The research method used is normative juridical with an analytical descriptive approach, using the Legislation Approach. This research uses the Law Approach by collecting and analyzing statutory provisions related to the environment and corporations. The legal material collection technique used is library research, then analyzed qualitatively. The results showed that there is legal protection for the owner of the toll road acquisition through consignment settlement.